PENGARUH PENAMBAHAN BAHAN ADITIF TERHADAP NILAI CBR CAMPURAN TANAH DAN FLY ASH UNTUK PENINGKATAN DAYA DUKUNG TANAH PADA PEKERJAAN JALAN - Orlando Domyzkiel Sasarari; Petrus Bahtiar; Dewi Ana Rusim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The performance of road pavement structures is highly dependent on the bearing capacity of the subgrade. However, subgrade soils in many locations exhibit inadequate bearing capacity, necessitating soil improvement through stabilization techniques. This study investigates the effect of incorporating 2% DIFA Soil Stabilizer on the soaked CBR of soil–fly ash mixtures intended for road construction applications. An experimental laboratory program was conducted using natural soil mixed with varying proportions of fly ash, followed by the addition of 2% DIFA Soil Stabilizer. The testing program included the determination of the physical properties of the soil and soaked CBR tests to evaluate the improvement in subgrade bearing capacity resulting from the different mixture compositions. The experimental results demonstrate that the incorporation of fly ash in combination with 2% DIFA Soil Stabilizer substantially enhances the soaked CBR of the soil. The highest soaked CBR value of 9.10% was achieved with the mixture containing 15% fly ash and 2% DIFA Soil Stabilizer, representing a significant improvement over the untreated natural soil, which exhibited a soaked CBR value of only 1.00%. These findings indicate that the combined use of fly ash and DIFA Soil Stabilizer is an effective stabilization approach for improving the engineering performance of subgrade soils and may serve as a viable alternative for enhancing the bearing capacity of road subgrades